REVIEW ON HIGH PRESSURE COLD SPRAY (HPCS) PROCESS AS CORROSION TREATMENT FOR AGING AIRCRAFT PART - Omar, Nooririnah; Abdullah, Rohana; Mustafa, Nuzaimah; Azhari, Muhammad azwar (2013)
The Asian region is forecast as fastest growing aviation market for the next 20 years. By 2025 Asian airports are expected to handle more than three times the volume of movement handled in 2005 with growing average 6% per year. Aircraft maintenance and repair play a major role in increasing useful life of aircraft part and on top of that, it increase confident level of user. Malaysia forecast to become regional maintenance, repairing and overhaul (MRO) hub to be worth US$65 billion by 2020.Corrosion treatment is one of the MRO services that utmost concern in the aircraft industry. Many techniques been used to control corrosion in aviation industry ; grease, application of advanced composite material, DOW 17 process and thermal spray. DOW 17 process issued with OSHA and thermal spray technology will create internal stress lead to fatigue failure due to application of heat on aircraft part. There is keen interest to explore potential applications of high pressure cold spray (HPCS) process onto aircraft structure for corrosion treatment. One of the characteristic of cold spray process is creates a negligible heat-affected zone in the as-deposited material and substrate, therefore generating layers that exhibit excellent fatigue characteristics and spray efficiency in HPCS reaching up to 90%. Due to this features, cold spray is potential solution for corrosion treatment to be applied on aircraft part.